OP0241 Anti-Flagellin Antibodies in Ankylosing Spondylitis (AS) Implicate Subclinical Bowel Inflammation and Differentiate as from Mechanical Back Pain Patients. (23rd January 2014) - Wallis, D.; Weisman, M.; Haroon, N.; Anton, A.; Mc Govern, D.; Targan, S.; Inman, R.
Abstract : Background: Serum antibody reactivity to microbial antigens may provide important clues to the role of gut-derived microbial antigens in ankylosing spondylitis (AS). Anti-flagellin (anti-CBir1) serum reactivity in Crohn's disease (CD) is associated with fibrostenosis and complicated small bowel CD. Response to CBir1 in CD is also significantly associated with the CD-associated NOD2 variants (1 ). Objectives: To compare the frequency of anti-flagellin (anti-CBir1) antibodies in patients with AS, AS and concomitant IBD and mechanical back pain. Methods: Sera from 79 patients with AS and concomitant inflammatory bowel disease (IBD), 78 age-matched patients with AS alone and 48 patients with mechanical back pain (MBP) were tested by ELISA for anti-flagellin (anti-CBir1) antibodies. Antibody positivity rates were compared using Fisher's exact test. ANOVA was performed to compare the median quantitative antibody level in ELISA units (EU) between the three groups. Results: The positivity rate and median quantitative antibody level of anti-CBir1 were higher in AS than in MBP patients (20.5% vs. 2.2%, p=0.003; 15 EU vs. 10 EU, p<0.001). The positivity rate and quantitative antibody level were also higher in patients with AS and concomitant IBD than in MBP (36.8% vs. 2.1%, p<0.0001; 18 EU vs. 10 EU, p<0.001). There was no significant difference in positivity rate or median quantitative antibody level between patients with AS alone and AS with concomitant IBD. Conclusions: Anti-flagellin antibodies are comparable between patients with AS alone and AS with concomitant IBD, and are significantly elevated in both groups compared with patients with mechanical back pain. These findings implicate subclinical bowel inflammation in AS and highlight the potential role of the gut microbiome in AS. References: Papadakis KA, Yang H, Ippoliti A, Mei L, Elson CO, Hershberg RM, Vasiliauskas EA, Fleshner PR, Abreu MT, Taylor K, Landers CJ, Rotter JI, Targan SR. Anti-flagellin (CBir1) phenotypic and genetic Crohn's disease associations. Inflamm Bowel Dis. 2007 May;13(5):524-30. Disclosure of Interest: None Declared